Multispectral optoacoustic tomography for non-invasive disease phenotyping in pediatric spinal muscular atrophy patients - Regensburger, Adrian; Wagner, Alexandra; Danko, Vera; Jüngert, Jörg M.; Federle, Anna; Klett, Daniel; Schüssler, Stephanie; Buehler, Adrian; Neurath, Markus; Roos, Andreas; Lochmüller, Hanns; Wölfle, Joachim; et al. (Photoacoustics, 2022)
Proximal spinal muscular atrophy (SMA) is a rare progressive, life limiting genetic motor neuron disease. While promising causal therapies are available, meaningful prognostic biomarkers for therapeutic monitoring are missing. We demonstrate handheld Multispectral Optoacoustic Tomography (MSOT) as a novel non-invasive imaging approach to visualize and quantify muscle wasting in pediatric SMA. While MSOT signals were distributed homogeneously in muscles of healthy volunteers (HVs), SMA patients showed moth-eaten optoacoustic signal patterns. Further signal quantification revealed greatest differences between groups at the isosbestic point for hemoglobin (SWL 800 nm). The SWL 800 nm signal intensities further correlated with clinical phenotype tested by standard motor outcome measures. Therefore, handheld MSOT could enable non-invasive assessment of disease burden in SMA patients.
CRIS-Team Scopus Importer:2021-11-26
Keywords: Multispectral optoacoustic tomography; Optoacoustics; Photoacoustics; Spinal muscular atrophie